Effect of green manufacturing in improving the product quality (Analytical research at Dar Al-Warith Printing and Publishing - Holy Karbala) - mahmood fahad, Yasir (Iraqi Journal for Administrative Sciences, 2024)
The research aimed to identify the effect of green manufacturing on the products quality of Dar Al-Warith Printing and Publishing Press. Data was collected using a questionnaire form. 80 employees out of 86 employees who were invited to participate in this survey responded to the form. The questionnaire included measuring key variables such as green manufacturing, which was measured in four dimensions (reducing waste, redesign, reuse, recycling), and product quality, which was measured in seven dimensions (Aesthetics, durability, ease of use, features, performance, reliability, serviceability) and the quantitative method was used in statistical analysis using the statistical program (spss.v.26). The results of this research showed that all dimensions of green manufacturing have a significant effect in explaining the changes that occur in the quality of products at the investigated printing press, except for the (redesign) dimension, the effect of which was insignificant.